Penerapan Manajemen Risiko Perbankan Syariah di Indonesia, Malaysia dan Brunei Darussalam - Anggraini, Putri Dewi; Sadewa, Manik Mutiara (P3M Politeknik Negeri Banjarmasin, 2024)
Islamic Financial Institutions in Indonesia are currently growing rapidly, including Islamic banks. After the global financial crisis, some experts argue that Islamic banks are more stable than conventional banks. Now banking in every country has regulations related to the implementation of risk management. The implementation of good risk management is expected to minimize risk in the future. Islamic banking in Indonesia, Malaysia, and Brunei Darussalam face greater risks in the future so that more and complex literacy is needed to be able to find out the application of risk management for Islamic banking. The data collection method in this research uses a literature study. The type of data used is qualitative data and the data source used in this research is secondary data in the form of documents or literature relevant to the title under study. The results showed that there are similarities in the active supervision of the Board of Directors, the Board of Commissioners and the Sharia Supervisory Board; the adequacy of risk management policies and procedures and the determination of risk limits; the process of identifying, measuring, monitoring and controlling risks and risk management information systems; internal control systems; and risk management organizations and functions in Islamic banking in Indonesia, Malaysia and Brunei Darussalam. In addition, there are differences in the types of risks that exist in these three countries.